Analisis Pengaruh Kepemilikan Institusional Terhadap Kinerja Keuangan Perusahaan - Nanda rahayu; Agus wahyudi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to investigate the impact of institutional ownership on company financial performance through qualitative research methods with a literature study approach. Institutional ownership, which involves entities such as investment companies, pension funds, and insurance funds owning shares in the company, is considered a crucial mechanism in corporate governance. Through a comprehensive review of various sources such as journals, books, and research reports, this study conducts a qualitative analysis to explore the complex relationship between institutional ownership and corporate financial performance. Findings from the literature highlight that this relationship is influenced by a variety of factors, including firm characteristics, other ownership structures, macroeconomic conditions, and management strategies. This research not only provides in-depth insights into the implications of institutional ownership for corporate governance, but also provides practical recommendations for companies, investors, and policymakers.